High-dose cytarabine chemotherapy (≥4 g/m2/day) before allogeneic hematopoietic stem cell transplantation for non-core-binding-factor AML in the first complete remission. Issue 13 (9th November 2020) - Nagahata, Yosuke; Kondo, Tadakazu; Ono, Yuichiro; Hiramoto, Nobuhiro; Kitano, Toshiyuki; Hishizawa, Masakatsu; Yamashita, Kouhei; Hashimoto, Hisako; Ishikawa, Takayuki; Takaori-Kondo, Akifumi
Abstract: Benefit of high-dose cytarabine (HD-AraC) for acute myeloid leukemia (AML) prior to allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains unknown. We retrospectively analyzed data from 79 non-core-binding-factor AML patients who underwent allo-HSCT in their first complete remission (CR1). In univariate analysis, HD-AraC (≥4 g/m 2 /day) before allo-HSCT improved disease-free survival (DFS) ( p  = .018), overall survival (OS) ( p  = .029), and cumulative incidence of relapse (CIR) ( p  = .033). Four-year DFS, OS, and CIR of patients receiving and not receiving HD-AraC were 79% vs. 49%, 82% vs. 56%, and 18% vs. 42%, respectively. In multivariate analysis, HD-AraC was a positive prognostic factor for DFS (hazard ratio (HR) = 0.36, 95% confidence interval (CI): 0.14–0.88), OS (HR  =  0.37, 95% CI: 0.14–0.99), and CIR (HR  =  0.38, 95% CI; 0.14–1.0). Our study demonstrates that HD-AraC before allo-HSCT at a dose ≥4 g/m 2 /day is effective for treating AML patients in CR1.